Air Hidup bagi Kaum Marjinal: Pembacaan Teologi Migran dari Yohanes 4:1-40 - Sukanto Limbong; Daniel Razsekar Panjaitan (Sekolah Tinggi Teologi Sumatera Utara, 2025)
This study highlights the urgency of a migrant theological reading of John 4:1–40 in light of global forced migration and marginalization, aiming to provide a relevant theological framework for the contemporary church. Employing a qualitative approach through exegetical, historical, and theological analysis of John’s narrative, combined with contextual reflection on the experiences of Indonesian migrant workers in Seberang Perai, Malaysia, the study demonstrates that Jesus’ journey through Samaria (dei) represents a divine imperative to cross ethnic, gender, and social boundaries. His encounter with the Samaritan woman reveals the promise of “living water” as a new identity that liberates the marginalized from social stigma. The study concludes that the church is called to become a “modern Jacob’s well,” a space of encounter, solidarity, and empowerment that transforms migrants from passive recipients into active agents of mission, while affirming an ecclesiology centered on migrants and the shared identity of believers as “pilgrim people” in Christ. AbstrakKajian ini menyoroti urgensi pembacaan teologi migran terhadap Yohanes 4:1–40 dalam konteks global migrasi paksa dan marginalisasi, dengan tujuan menghadirkan kerangka teologis yang relevan bagi gereja masa kini. Penelitian ini menggunakan pendekatan kualitatif dengan analisis eksegetis, historis, dan teologis terhadap teks Yohanes, dipadukan dengan refleksi kontekstual pada pengalaman Pekerja Migran Indonesia di Seberang Perai, Malaysia. Hasil penelitian menunjukkan bahwa perjalanan Yesus melintasi Samaria (dei) merupakan keharusan ilahi yang menegaskan misi untuk melintasi batas etnis, gender, dan sosial, sementara perjumpaan-Nya dengan perempuan Samaria menyingkapkan janji “air hidup” sebagai identitas baru yang membebaskan kaum marjinal dari stigma sosial. Studi ini menyimpulkan bahwa gereja dipanggil menjadi “Sumur Yakub modern,” yakni ruang perjumpaan, solidaritas, dan pemberdayaan yang mengubah migran dari penerima pasif menjadi agen misi aktif, sekaligus menegaskan eklesiologi yang berpusat pada migran dan identitas umat sebagai “peziarah” dalam Kristus.